Manipulative Language in Cyber Grooming: A Pragmatic Analysis of Speech Acts and Power Relations - Mannahali, Misnah; Angreany, Femmy (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Cyber grooming constitutes a form of online abuse in which language plays a central role in establishing trust, manipulating emotions, and gradually exerting control over victims. This study investigates how manipulative language is pragmatically constructed in cyber grooming interactions, with particular attention to speech acts and the reproduction of power relations between perpetrators and victims. Employing a mixed-methods sequential exploratory design, the research combines qualitative pragmatic analysis of cyber grooming messages with quantitative mapping of recurring linguistic patterns. The data consist of digital conversation excerpts from reported cyber grooming cases, analyzed using speech act theory and a critical perspective on power and interactional asymmetry. The findings reveal that perpetrators strategically deploy directive, commissive, and expressive speech acts to normalize intimacy, reduce victims’ resistance, and legitimize asymmetrical control. These speech acts are frequently embedded in linguistic strategies such as emotional reassurance, simulated care, urgency framing, and implicit threats, which collectively function to manipulate victims’ cognition and emotional responses. The study further demonstrates that manipulative language in cyber grooming operates as a gradual process, shifting from seemingly benign relational discourse to coercive and controlling communication as power relations become increasingly unequal. By foregrounding the pragmatic mechanisms of manipulation, this research contributes to a deeper linguistic understanding of cyber grooming and offers empirically grounded insights that may inform early detection frameworks, digital safety education, and child protection policies.